Stereotactic radiation therapy for canine multilobular osteochondrosarcoma: Eight cases. (17th June 2019) - Sweet, Katherine A.; Nolan, Michael W.; Yoshikawa, Hiroto; Gieger, Tracy L.
Abstract: Radiotherapy is often considered in the management of canine multilobular osteochondrosarcoma (MLO), but its efficacy against bulky MLO tumours is poorly described. This retrospective case series describes the clinical outcomes of pet dogs with MLO treated with a stereotactic radiation therapy (SRT) prescription of 30 Gy in three consecutive daily 10 Gy fractions. Dogs with an imaging (via computed tomography [CT] scan) and/or pathologic diagnosis of MLO were included. Patient demographics, tumour characteristics, radiation plan dosimetry, toxicity and outcome data were obtained retrospectively from the records. The median progression‐free survival time (MPFST) and median overall survival time (MST) were calculated using a LOGLOG test. Eight dogs were included. None had evidence of metastasis at the time of SRT. Clinical signs associated with the MLO included a mass noted by owner, stertor, vestibular signs, exophthalmos and abnormal mentation. Of the five dogs that had CT scans performed 3 to 9 months after SRT, tumour volume decreased by 26% to 87% in four dogs and increased by 32% in one dog. Late radiation toxicity was documented in three dogs (VRTOG Grade 1 skin and/or ocular, n = 2; Grade 3 central nervous system, n = 1). Confirmed local disease progression (n = 3; two were treated with a second course of SRT) and suspected pulmonary metastasis (n = 2) occurred 90 to 315 days after SRT. The MPFST was 223 days (interquartile range [IQR]: 144.5‐276.5 days). The MST was 329 days (IQR: 241.5‐408 days). This protocol was well‐tolerated, but the duration of response was short‐lived.